Propping up predicates: Adjectival predication in Tłı̨chǫ Yatıì - Welch, Nicholas (Glossa: a journal of general linguistics, 2016)
In Tłı̨chǫ Yatıì (Dene, aka Athapaskan), copulas appear obligatorily with adjectives predicated of animate subjects, but are barred from appearing with adjectives predicated of inanimates. I propose that this asymmetry arises from a requirement to realize grammatical agreement for person, and that animate nouns alone bear a person feature. Unlike verbs, adjectives in this language cannot inflect; hence copulas are inserted in adjectival predicates as a rescue strategy to avoid ungrammaticality.